Conflict and Integration: The Mujahidin Mosque Case Study (A Perspective of Conflict Theory and Fiqh al-Ikhtilaf) - Nasiri (STAI Syaichona Moh. Cholil Bangkalan, 2023)
The conflict at the Mujahidin mosque arose from two root causes: first, a misunderstanding between Moel and Latif regarding Moel's desire to give tafsir lectures at the Mujahidin mosque. Second, a difference of opinion regarding the position of the saff. Moel and his supporters wanted to change the saff to match the position of the mosque building, while Latif and his supporters wanted to maintain the position of the saff so that it continued to face the right corner of the mosque, as this position was in line with the direction of the qibla. According to Dahrendorf, the conflict that occurred at the Mujahidin mosque was natural because conflict and differences lead to peace and equality. This is evident in what is happening at the Mujahidin mosque today. After a prolonged conflict from 1998 to 2016, with coordination and awareness from each of the conflicting parties, the conflict finally ended and became a beautiful peace.